NURSES’ OCCUPATIONAL STRESS IN EMERGENCY CARE AND ISOLATION WARDS AFTER SECOND AND THIRD WAVE OF COVID-19 - Nurfika Asmaningrum; Aldi Rahardian Pujiyono; Kholid Rosyidi M Nur; Ida Zuhroidah (Nurse and Health)
Background: COVID-19 pandemic caused globally public health crises. The massive spread of COVID-19 cases put nurses under immense stress due to high workload and thus high risk of infection, especially those in Emergency Room (ER) and Isolation Wards (IW). Both units were actively involved in handling COVID-19 as the first screening and treatment were given to COVID-19 patients.